Safety and immunogenicity of a live attenuated Rift Valley Fever recombinant arMP-12ΔNSm21/384 vaccine candidate for sheep, goats and calves. Issue 12 (14th March 2019) - Boumart, Z.; Daouam, S.; Bamouh, Z.; Jazouli, M.; Tadlaoui, K.O; Dungu, B.; Bettinger, G.; Watts, D.M.; Elharrak, M.
Highlights: RVF arMP-12ΔNSm21/384 vaccine virus was evaluated as a potential veterinary vaccine. Vaccine virus infectivity titers in Vero cell were suitable for vaccine production. arMP-12ΔNSm21/384 vaccine candidate was safe in domestic sheep, goats and calves. Immunogenicity was characterized by detectable and sustained antibody in all animals. arMP-12ΔNSm21/384 is a promising candidate for preventing RVF in African ruminants. Abstract: Rift Valley fever (RVF) causes serious health and economic losses to the livestock industry as well as a significant cause of human disease. The prevention of RVF in Africa is a global priority, however, available vaccines have only been partially effective. Therefore, the objective of this study was to evaluate the safety and immunogenicity of a live, attenuated recombinant RVFV arMP-12ΔNSm21/384 nucleotide deletion vaccine candidate in domestic ruminants. Evaluation involved testing to determine the infectivity titer of the vaccine virus in Vero cells for industrial scale up vaccine production. Safety experiments were conducted to determine the potential of the vaccine virus to revert to virulence by serial passages in sheep, the possibility of virus spread from vaccinated sheep and calves to unvaccinated animals, and the potential health effects of administering overdoses of the vaccine to sheep, goats and calves. The immunogenicity of 3 doses of 10 4, 10 5 and 10 6 Tissue Culture Infectious Doses50% (TCID50 ) of the vaccine was assessed in 3 groups of 10 sheep and 3 groups of 10 goats, and doses of 10 5, 10 6 and 10 7 TCID50 was evaluated in 3 groups of 10 calves subcutaenous vaccintation. The results showed that the infectivity titer of the vaccine virus was 10 8.4 TCID50 /ml, that the vaccine did not spread from vaccinated to un-vaccinated animals, there was no evidence of reversion to virulence in sheep and the vaccine overdoses did not cause any adverse effects. The immunogenicity among sheep, goats and calves indicated that doses of 10 4 –10 6 TCID50 elicited detectable antibody by day 7 post-vaccination (PV) with antibody titers ranging from 0.6 log to 2.1 log on day 14 PV with sustained titers through day 28 PV. Overall, these findings indicated that the RVFV arMP-12ΔNSm21/384 vaccine is a promising candidate for the prevention of RVF among domestic ruminants.